2013
DOI: 10.1111/clr.12216
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different surgical drilling procedures on full laser‐etched microgrooves surface‐treated implants: an experimental study in sheep

Abstract: The laser-etched microgrooved implant presented osteoconductive and biocompatible properties for all surgical procedures tested. However, procedures providing increasingly higher press-fit scenarios presented the strongest histomorphometric and biomechanical responses at 3 and 6 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…These results confirmed that a simplified drilling protocol does not have negative indications and it achieves at least comparable or faster osseointegration than the conventional drilling procedure, with gradual expansion of the implant site 34,35 .…”
Section: Discussionsupporting
confidence: 72%
“…These results confirmed that a simplified drilling protocol does not have negative indications and it achieves at least comparable or faster osseointegration than the conventional drilling procedure, with gradual expansion of the implant site 34,35 .…”
Section: Discussionsupporting
confidence: 72%
“…This has been indicated in our previous study that the less stable implant created by overdrilling do not contribute to subsequent osseointegration (Jimbo et al. ,b).…”
Section: Discussionmentioning
confidence: 55%
“…Theoretically, it has been suggested that the bone is an elastic material before its yielding point, which is an indication that a certain level of strain can be tolerated due to a relaxation effect (Jimbo et al. ,b). On the other hand, once the strain in the bone exceeds the yielding point, numerous microfractures along with blood capillary overcompression provoke ischemic necrosis or in the worst scenario, complete bone fracture (Bashutski et al.…”
mentioning
confidence: 99%
“…It is a fact that primary or mechanical stability is required to have biologic integration, 52 particularly in scenarios in which immediate implant loading is to be applied. However, although recent literature 53 states that even over‐drilled implants can achieve osseointegration, its degree still remains unclear. Early studies demonstrated higher implant success rate in the mandible because of its cortical (or compact) bone compared to the maxilla in which the cancellous bone presents with a more porous architecture 18 , 54 .…”
Section: Discussionmentioning
confidence: 99%